Професійна підготовка фахівців ветеринарного профілю у ВНЗ Німеччини - Пилипенко, Олена Петрівна (НУБіП України, 2018)
Дисертація на здобуття наукового ступеня кандидата педагогічних наук зі спеціальності 13.00.04 «Теорія і методика професійної освіти». Національний університет біоресурсів і природокористування України. Київ, 2018. Дисертаційну роботу присвячено дослідженню питань професійної підготовки фахівців ветеринарного профілю у вищих навчальних закладах Німеччини. Розкрито особливості структури, змісту, форм, методів навчання та контролю у процесі професійної підготовки фахівців ветеринарного профілю у Німеччині, до яких належать блочно-модульна технологія, міждисциплінарна структуризація змісту навчання, ротаційний рік, одноцикловість підготовки зі складанням державного іспиту, акцент на вивченні дисциплін, пов’язаних з харчовою безпекою. Представлено структурну модель професійної підготовки лікаря ветеринарної медицини у ветеринарних вищих начальних закладах Німеччини, що унаочнює навчальний процес і відображає взаємодію трьох основних блоків: теоретичного, змістового і процесуального. Схарактеризовано основні історичні етапи розвитку вищої ветеринарної освіти Німеччини. З’ясовано особливості критеріїв вступу до вищих навчальних закладів Німеччини, які здійснюють підготовку майбутніх фахівців ветеринарного профілю. Проаналізовано структуру і зміст навчальних програм підготовки фахівців ветеринарного профілю в університетах Німеччини й України. Обґрунтовано доцільність використання досвіду німецьких вищих навчальних закладів у процесі професійної підготовки фахівців ветеринарного профілю в Україні (збільшення частки варіативної складової навчального плану, посилення практичної підготовки, запровадження клінічно-практичного року підготовки фахівців ветеринарного профілю)
The thesis for the scientific degree of the Candidate of Pedagogical Sciences by the speciality 13.00.04 Theory and Methodology of Vocational Education. National University of Life and Environmental Sciences of Ukraine. Kyiv, 2018. In the dissertation «Professional training of economics teachers at higher educational institutions of Germany» the theoretical and practical bases of vocational training of veterinary at German universities were investigated, recommendations on the use of positive experience in the training of veterinary at universities of Germany in higher education institutions in Ukraine were developed and suggested. The state of research of the problem of vocational training of veterinary of Germany in pedagogical science and practice was analyzed, foreign educational systems of veterinary professional training of veterinary were analyzed, the leading tendencies of 6 vocational training of veterinary teachers for vocational education institutions in German universities were determined. Extended interpretation of such concepts: «integrated lesson», «practical or rotational year» – as a result of the study of the theoretical gains of German scientists in the identified scientific direction. The integrated training (Querschnittsunterricht) provides the implementation of interdisciplinary connections between clinical, preclinical, paraclinical disciplines and food safety disciplines when implementing interdisciplinary programs. Practical or rotational year (Rotationsjahr) is an integrative part of the training of future specialists in the veterinary field in the university’s professional practice in clinics, which is held in the 9th and 10th semesters, which allows you to successfully develop effective clinical thinking, stimulate and intensify cognitive activity of students. A comparative analysis of the curricula of vocational training of veterinary specialists at the universities of Germany and institutions of higher education of Ukraine was carried out and general and excellent characteristics of vocational training at Ukrainian and German universities were generalized. The differences include the restriction of the «number clause» in the procedure for entering the university’s veterinary profile, the preparation of the State Examination at the end of the training of veterinary medicine doctors, the definition of the content of higher veterinary education by approbation documents, the orientation of the training of veterinary specialists for scientific research and practical activities, the availability of special training formats: problem-oriented education (POL), stimulation training (Simulationen), training in skills-labs, implementation of the «practical year». The scientific novelty of the obtained results is that: for the first time in the theory of native vocational education certain features of the structure, content, forms, methods of teaching and control of the success in the process of vocational training of veterinary specialists at the universities of Germany are defined (block-modular technology, interdisciplinary structuring of the content of training, rotational year, single-cycle training with the compilation of a state exam, emphasis on studying disciplines related to food safety). The structural model of vocational training of the veterinary medicine doctor in the veterinary universities of Germany is presented, which illustrates the educational process and reflects the interaction of the three main blocks: theoretical, substantive and procedural; the main historical stages of the development of higher veterinary education in Germany are outlined and characterized; the peculiarities of the criteria for admission to higher education institutions of Germany, which are preparing future specialists in the veterinary field (numerus clause, pre-training practice, quotas on the waiting period, taking into account social criteria) are determined; the structure and content of training programs for the training of veterinary specialists at the universities of Germany have been analyzed; the expediency of using the experience of German higher education institutions in the process of vocational training of specialists in the veterinary profession in Ukraine (increase of the share of the variable component of the curriculum, strengthening of practical training, introduction of a clinical and practical year for the training of specialists in the veterinary profile) was substantiated; Further development of the idea of improving the theoretical and practical training of future specialists in the veterinary profile on the basis of the progressive experience of higher education institutions in Germany (simulation training, optimization of the structure of independent work of students)
Keywords: професійна підготовка; методи; форми; виробнича практика; майбутній ветеринар; міждисциплінарність; блочно-модульна технологія; vocational training; veterinary specialists; veterinary medicine doctors; training; semester; higher education; interdisciplinarity; block-modular technology